DOI: 10.35537/10915/4412
|View full text |Cite
|
Sign up to set email alerts
|

Estudios morfológicos y ultraestructurales en esporas de Cyatheaceae del Cono Sur

Abstract: Se estudió la morfología y la ultraestructura de las esporas de las Cyatheaceae del Cono Sur (Argentina, Chile, Paraguay, Uruguay y los tres estados del sur de Brasil). Para realizar este trabajo se utilizó material de herbario y fresco, coleccionado en viajes de campo. Se usaron diversas técnicas de fijación y tinciones diferenciales y las observaciones se realizaron con microscopio óptico y electrónico de barrido y de transmisión. Las Cyatheaceae que crecen en el área de estudio corresponden a tres géneros, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the last few years, the wall morphology and ultrastructure of Cyatheaceae spores from southern South America have been widely studied (Marquez 2009;Marquez et al 2009Marquez et al , 2010aMarquez et al , 2010b, and it has been observed that the features of the spores are typical of each genus.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the wall morphology and ultrastructure of Cyatheaceae spores from southern South America have been widely studied (Marquez 2009;Marquez et al 2009Marquez et al , 2010aMarquez et al , 2010b, and it has been observed that the features of the spores are typical of each genus.…”
Section: Introductionmentioning
confidence: 99%